Global burden of 369 diseases and injuries in 204 countries and territories, 1990–2019: A systematic analysis for the Global Burden of Disease Study 2019 - GBD 2019 Diseases and Injuries Collaborators (Elsevier, 2022)
This article was published in The Lancet [ © 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access Article under the CC BY 4.0 license..] and the definite version is available at: https://doi.org/10.1016/S0140-6736(20)30925-9 The Journal's website is at: https://reader.elsevier.com/reader/sd/pii/S0140673620309259?token=2A7E3F77FD7BD7D4FE0CF92341AEC3228D64FEE861A2B2692E06DC7F76E21E9CD7583FAED7F2A7806A39EF60A6150C5F&originRegion=eu-west-1&originCreation=20220522055436